Avaliação de mecanismo cinético químico reduzido na predição de emissão de poluentes específicos por motores de combustão interna para misturas de gasolina e etanol - Clarissa de Moraes Martins (2018)
In Brazil, the automotive sector consists in one of the main sources of air pollution in urban areas. Exhaust gases from internal combustion engines may containpollutantsasnitrogenoxides,carbonmonoxide,unburnedandpartiallyburned hydrocarbons and soot, which are responsible for environmental and human health problems. International regulations for emission of pollutants as well as current nationalprogramstostimulatetheautomotiveindustry,suchastherecentlyapproved Rota 2030, make emissions levels for this sector increasingly strict. As a result, the development of more efficient engines and the use of alternative fuels have become even more relevant. The use of ethanol as an additive to gasoline has proved to be an efficient alternative in Brazil by reducing the dependence on fossil fuels and vehicular emissions of greenhouse gases. Thus, it is necessary an in-depth study of the combustion process of ethanol and gasoline mixtures in internal combustion engines. With this in mind, the finite volume method together with reduced chemical kineticmechanismshavebeenlargelyapplied.However,moststudiesfoundonliterature report numerical analysis of compression ignition engines. Thus, the objective of this work is to evaluate the prediction of specific pollutants (CO, CO2, NOx and HC) in an internal combustion engine by applying a reduced chemical kinetic mechanism with 75 species and 343 chemical reactions to model the combustion process. The methodology consists in carrying out numerical simulations of an internal combustion engine operating with different gasoline and ethanol mixtures as fuel (E22, E50, E85 and E100) at the same engine speed and load. The emissions calculated in the computational models were evaluated qualitatively observing the trendinemissionsdatafordifferentmixturesandbasedontheexperimentalresults obtained from the database of Centro de Tecnologia da Mobilidade (CTM-UFMG). The results showed a hight reactivity level of the chemical kinetic mechanism for the fuel E22 indicating that the chemical kinetic mechanism can be improved. The air-fuel mixture impacted the emissions of CO2, CO and HC due to the formation of regions with excess of fuel in the cylinder. However, it could be observed, as indicated by studies in literature, the reduction of NOx for the mixtures with higher content of ethanol in the fuel. It is concluded then, that for the prediction of combustion and pollutant emissions, the reduced chemical kinetic mechanism used in this work needs adjustments and the numerical modeling of the formation of the mixture for multicomponent fuels can be improved